2018
DOI: 10.9767/bcrec.14.1.2258.142-152
|View full text |Cite
|
Sign up to set email alerts
|

PEGylated MoS2 Nanosheets: A Dual Functional Photocatalyst for Photodegradation of Organic Dyes and Photoreduction of Chromium from Aqueous Solution

Abstract: This article reports the synthesis of PEGylated microspheres of MoS2 nanosheets through the hydrothermal method and its application in rhodamine B and methylene blue dyes photodegradation, and photoreduction of chromium(VI) to chromium(III) in water under illumination with visible light. The catalyst was characterized using X-ray Diffraction (XRD), Transmission Electron Microscopy (TEM), Field Emission Scanning Electron Microscopy (FESEM), Energy Dispersive X-ray Spectroscopy (EDS), Fourier Transform Infra Red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Fortunately, the preparation of ZnS composites with narrow band gap semiconductor nanomaterials is an effective and widely used method to extend visible light absorption and improve the photocatalytic efficiency. Noble metal-free MoS 2 -based nanocomposites have also emerged as efficient photocatalysts having broad photocatalytic applications, such as energy generation and water treatment, owing to their large surface area, narrow band gap, low cost, visible light response, and complex edges having a highly unsaturated nature. However, the small band gap of single-layer MoS 2 (approximately 1.9 eV) limits its photocatalytic efficiency owing to the rapid recombination of charge carriers. Several attempts have been made to delay the recombination of charge carriers, such as the fabrication of MoS 2 nanosheets with wide-band-gap semiconductor nanomaterials (e.g., TiO 2 , Bi 2 O 3 , CdS, and ZnS) in order to enhance their potential for the degradation of organic water contaminants. ,, Thus, ZnS/MoS 2 heterostructure nanocomposite materials have been studied as photocatalysts with improved photocatalytic potential compared to pure nanosized MoS 2 and ZnS. , For example, Jeon et al prepared ZnS loaded with MoS 2 nanoflakes and observed that the photocatalytic performance of the ZnS/MoS 2 nanocomposite was enhanced compared to those of pristine ZnS and MoS 2 because of the enhanced surface area.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, the preparation of ZnS composites with narrow band gap semiconductor nanomaterials is an effective and widely used method to extend visible light absorption and improve the photocatalytic efficiency. Noble metal-free MoS 2 -based nanocomposites have also emerged as efficient photocatalysts having broad photocatalytic applications, such as energy generation and water treatment, owing to their large surface area, narrow band gap, low cost, visible light response, and complex edges having a highly unsaturated nature. However, the small band gap of single-layer MoS 2 (approximately 1.9 eV) limits its photocatalytic efficiency owing to the rapid recombination of charge carriers. Several attempts have been made to delay the recombination of charge carriers, such as the fabrication of MoS 2 nanosheets with wide-band-gap semiconductor nanomaterials (e.g., TiO 2 , Bi 2 O 3 , CdS, and ZnS) in order to enhance their potential for the degradation of organic water contaminants. ,, Thus, ZnS/MoS 2 heterostructure nanocomposite materials have been studied as photocatalysts with improved photocatalytic potential compared to pure nanosized MoS 2 and ZnS. , For example, Jeon et al prepared ZnS loaded with MoS 2 nanoflakes and observed that the photocatalytic performance of the ZnS/MoS 2 nanocomposite was enhanced compared to those of pristine ZnS and MoS 2 because of the enhanced surface area.…”
Section: Introductionmentioning
confidence: 99%
“…6b). 48,49 The characteristic peak of the MoS 2 nanosheets at 455 cm −1 is also observed. The peaks observed at 809 and 1079 cm −1 are due to the stretching and bending of Si–O–Si bonds in the PDMS matrix, respectively.…”
Section: Resultsmentioning
confidence: 82%
“…The band at 659.3 cm −1 is also derived from the C-C vibration of the PEG skeleton, as well as the intense band at 817.2 cm −1 [42,44,45]. The band at 992.7 cm −1 refers to the stretching and bending mode of the O-H bonds and the stretching of the C-C bonds, which is well defined and more intense for primary alcohols, as is the case with PEG [34,[46][47][48][49]. The MoS2-PEG/Au hybrid presented the same bands as the MoS2-PEG, but with the additional band at 1493.0 cm −1 ascribed to γ(C-C) from PEG which was intensified due the presence of gold nanostructures [50].…”
Section: Characterization Of Flower-like Mos 2 -Peg/aumentioning
confidence: 99%